Implementation of sustainable public procurement in China: An assessment using quantitative text analysis in large-scale tender documents - Cao, Fuguo; Li, Runyu; Cao, Xiaoyan (Frontiers in Environmental Science, 2022)
In recent years, an increasing amount of attention has been paid worldwide to the sustainable development of the economy and society. Because of its size and prevalence, public procurement has always been a powerful policy tool used to tackle issues related to the sustainability of the society, economy, and environment. China has attached high priority to sustainable development, and many aspects of sustainable public procurement (SPP) have been implemented though no official documents have referred to the concept of SPP. Therefore, little is known about the actual implementation and pattens of SPP in practice. The purpose of the study is to assess the actual implementation and patterns of SPP in China. We obtained 42,369 public procurement documents for 2015-2020 using web crawler technique and the actual implementation of SPP was assessed through text-mining technique. The research shows that SPP is implemented in more than 82% of the documents and appears an upward trend in the past 6 years. Several patterns of SPP implementation are also identified. First, most documents implement more than one category of SPP. Second, small and medium-sized enterprises-oriented procurement is the most implemented SPP main category, overtaking environmentally friendly procurement only by a small margin, and the procurement for the circular economy is the least implemented. Third, there seem to be some relationships between the level of SPP implementation and the award method, tender price and contract type. Finally, there is a substantial transformation of China’s SPP towards social aspects of SPP in recent years. Policy implications, limitations and issues for future studies are also discussed.